Determination of the orbital moment and crystal field splitting in LaTiO3 - Haverkort, Maurits W. (Arxiv, 2004)
Utilizing a sum-rule in a spin-resolved photoelectron spectroscopic experiment with circularly polarized light, we show that the orbital moment in LaTiO$_3$ is strongly reduced both below and above the Néel temperature. Using Ti $L_{2,3}$ x-ray absorption spectroscopy as a local probe, we found that the crystal field splitting in the $t_{2g}$ subshell is about 0.12-0.30 eV. This large splitting does not facilitate the formation of an orbital liquid.
Im Titel ist "3" tiefgestellt
Gesehen am 28.11.2017